Competitividade e impacto nas agroindústrias de origem animal com certificação da equivalência do selo SIM/SISBI - Both, Marcelo (2024)
This study investigates the impact of SISBI (Brazilian Animal-Origin Product Inspection System) certification on the competitiveness of animal-origin agribusinesses. SISBI certification allows products inspected at the municipal level by SIM (Municipal Inspection Service) to be sold nationwide, significantly expanding accessible markets. The methodology combined bibliographic, documentary, experimental, ex-post-facto, survey, field research, case study, action research, and participant analysis methods. Bibliographic and documentary research, based on Prodanov and Freitas (2013), utilized published materials and official records, while experimental and ex-post-facto research evaluated the impact of certification. Results confirm that technical inspection enhances competitiveness, resulting in improved product quality and market expansion, especially for small and medium enterprises. Process standardization and increased consumer confidence boost demand and customer loyalty, while public policies, such as Decree No. 9.013 of 2017, support sanitary compliance and competitiveness.